2011
DOI: 10.1111/j.1365-2710.2011.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in genotype and allele frequency distributions of polymorphic drug metabolizing enzymes CYP2C19 and CYP2D6 in mainland Chinese Mongolian, Hui and Han populations

Abstract: This is first report of interethnic differences in frequencies of functional CYP2C19 and CYP2D6 genes among Chinese Mongolian, Hui and Han populations. These differences may be important in explaining reported inter-ethnic differences in disease prevalence and response to drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Two hundred and eleven studies not fulfilling the eligibility criteria were further excluded. Finally, a total of 86 studies were included in this review. These included 25, 24, 20 and 17 studies on CYP2C9 , CYP2C19 , CYP2D6 and CYP3A5 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Two hundred and eleven studies not fulfilling the eligibility criteria were further excluded. Finally, a total of 86 studies were included in this review. These included 25, 24, 20 and 17 studies on CYP2C9 , CYP2C19 , CYP2D6 and CYP3A5 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[13] found that the allele frequencies of CYP2C19*2 were respectively 29.7%, 32.4% and 18.2% in Han, Hui and Mongolian, the allele frequencies of CYP2C19*3 were respectively 7.9%, 10.2% and 11.2% in Han, Hui and Mongolian. Other literatures [14,15] reported that the allele frequencies of CYP2C19*2 were 11.1% for Western Africa, 14.0% for Western Europe and 16.3% for Northern Europe respectively, and the allele frequencies of CYP2C19*3 were 0% for Western Africa, 0.2% for Western Europe and 0.2% for Northern Europe respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Trials conducted in East Asia have reported the frequency of PM phenotype in the range 17–23% in healthy Asians, 9–28% in Chinese, and only 2–5% in healthy Caucasians. The biggest inter‐ethnic difference for the CYP2C19 PM phenotype is reported between Chinese Hui and Dai minorities (25% vs 9.3%, respectively) …”
Section: Ethnic Distribution Of Cyp2c19 Polymorphisms—is It Clinicallmentioning
confidence: 97%
“…The biggest inter-ethnic difference for the CYP2C19 PM phenotype is reported between Chinese Hui and Dai minorities (25% vs 9.3%, respectively). 58,59 Association of CYP2C19 alleles and risk of cardiovascular adverse events. An increasing number of studies conducted in Asian countries show that reduced function CYP2C19 alleles are associated with an increased risk of vascular events.…”
Section: Introductionmentioning
confidence: 99%